Pemodelan Spasial Pengaruh Ruang Terbuka Hijau (RTH) Dengan Mengukur Tingkat Kadar Gas (Karbon Monoksida) (Studi Kasus: : Kelurahan Entrop Distrik Jayapura Selatan) - Lodewijk.E.S.Rumere; Monita Y. Beatrick; Elisabeth V. Wambrauw (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
This research aims to model the impact of Green Open Space (GOS) on Carbon Monoxide (CO) gas levels in Entrop Village, South Jayapura District. Green Open Space plays a crucial role in improving air quality in an area. In the context of rapid urbanization and increasing motor vehicle numbers, GOS serves as the city's lungs, capable of absorbing pollutants and improving air quality. The research method used is spatial modeling, which allows mapping the distribution of GOS and measuring CO levels on the main roads of Entrop Village. Primary data was obtained through field surveys using CO measuring instruments, while secondary data was obtained from various literature sources and reports from related agencies. Data analysis was conducted using statistical and spatial approaches to identify the relationship between GOS and CO levels. The results showed a significant negative relationship between the extent of GOS and CO levels. The larger the GOS area, the lower the CO concentration in the area. Spatial modeling also identified high CO concentration points in areas with low GOS density. Furthermore, this research found that uneven distribution of GOS contributes to variations in air quality (CO) in different locations. These findings highlight the importance of effective GOS management as part of air pollution control strategies in large cities. Recommendations from this research include increasing the number and distribution of GOS in areas with high CO concentrations, and integrating GOS into urban spatial planning to create a healthier and more sustainable environment. This research makes a significant contribution to sustainable urban planning by emphasizing the importance of integrating GOS into spatial planning to improve air quality and environmental health. Thus, the results of this research can serve as a reference for the government and stakeholders in formulating future GOS management and air pollution control policies.